Concurrent prescribing: Evaluation of its knowledge among dentists - Sharma, Amit (Natl J Maxillofac Surg, 2019)
INTRODUCTION: Considering the staggering number of drugs being prescribed to the patients for dental ailments, the ability of the dentists to recognize potential drug–drug interactions (DDIs) is essential to reduce their occurrence. This study aims to assess the dentist's ability to recognize the potentially clinically significant DDIs in clinical practice. SUBJECTS AND METHODS: This questionnaire-based study was carried out among the dentists working at private tertiary care teaching dental hospitals in Jaipur city. Eighty-five dentists working as faculty members in various departments and having postgraduate degree in their respective specialty were enrolled after taking their written informed consent. A prevalidated close-ended questionnaire was given to the respondents to check their knowledge about common DDI possible in clinical dentistry practice. STATISTICAL ANALYSIS USED: Statistical analysis was done using descriptive statistics. Data were collected in a predesigned Microsoft Excel 2010. Continuous variables were presented as mean values ± standard deviation, and categorical variables were presented as percentages. RESULTS: Among 85 dentists recruited for the study, no one had knowledge about all the common DDIs in dental practice. The participants could correctly identify only 47.86% of drug pairs. Drug information services available on the Internet were the most common source (32%) of knowledge of DDIs among them. Knowledge of the prescribed drug (40%) and complete drug history including over-the-counter and herbal products (35%) were the two important ways identified by them for avoiding unwanted drug interactions in clinics. CONCLUSION: The study revealed that the existing knowledge of the dentists was not adequate. Hence the knowledge of the dentists about DDIs pertinent to dentistry should be enriched and should be reinforced by arranging training sessions at constant intervals of time.